Butylated hydroxytoluene does not protect Chinese hamster ovary cells from chromosomal damage induced by high-dose rate 192Ir irradiation - Grillo, Claudia Alejandra (2006)
Previous reports showed the protective effect of the synthetic antioxidant butylated hydroxytoluene (BHT) against the chromosomal damage induced by bleomycin (BLM), cadmium chloride and potassium dichromate. To test the hypothesis that this effect was exerted by inhibition and/or scavenging of reactive oxygen species (ROS), the effect of BHT on the chromosomal damage induced by a high dose-rate gamma rays (HDR 192Ir). Experiments were carried out by irradiating G1 CHO cells with nominal doses of 1, 2 or 3 Gy. BHT (doses of 1.0, 2.5 or 5.0 μg/ml) was added to the culture immediately before or immediately after irradiation. Cells were then incubated in the presence of BHT for 13 h until harvesting and fixation. Results obtained showed that BHT did not decrease the chromosomal damage induced by radiation in any consistent fashion. On the contrary, in cells post-treated with 5.0 μg/ml of BHT the yield of chromosomal aberrations increased in several experimental points. These results with ionizing radiation suggest that the previous observed protective effects of BHT on the chromosomal damage induced by chemical genotoxicants may not be mediated solely through the scavenging or inactivating reactive oxidative species. The decrease of the yield of chromosomal damage induced by BLM could be due to the union of BHT with a metallic ion, in this case Fe (II), required for the activation of BLM. In the same way, the protective effect of BHT on the chromosomal damage induced by cadmium chloride and potassium dichromate could be due to the decrease of the effective dose of both salts in the cell through the chelation of the cations by BHT.